Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pasien Pre Operasi Di Rumah Sakit Rekso Waluyo Mojokerto - Arifin Nurbiyanto (MEDICA MAJAPAHIT, 2012)
The process of hospital treatment often ignore the psychological aspects of giving rise to a variety of psychological problems for the patient, one of which is anxiety. Anxiety is the most common feelings experienced by patients treated in the hospital, especially in patients who will unde